Development of Gateball Sports E-Module to Improve Student Learning Outcomes: Bahasa Inggris - Siti Fahwiza, Siti Fahwiza; Suprayitno, Suprayitno; Nurkadri, Nurkadri (Indonesian Journal of Sport Management, 2024)
This research is based on problems that occur in the field, namely that there is no gateball sports learning module, especially electronic-based, and there are still many students who cannot perform stroke and sparking techniques in the final exam test, so the development of e-modules is expected to improve student understanding and learning outcomes. after being given treatment. The novelty of the development of this e-module is in terms of packaging information on punch technique demonstration tutorials that can be easily understood by readers by providing direct examples through moving images and videos that can be clicked to enlarge. The type of research used is Pre-Experimental with a One Group Pretest-Posttest design. The subjects in this research were material experts, media experts, linguists, lecturers who taught gateball elective courses from Medan State University (UNIMED), 10 UNIMED students as small group trial samples and 30 STOK Binaguna Medan students as group trial samples big. E-module development follows Borg and Gall's theory with 10 stages. Validation shows the percentage of material experts is 94%, media experts are 93%, language experts are 68%, and lecturers are 98%. The increase in learning outcomes was analyzed using the T-Test and N-Gain, with an N-Gain result of 0.75 which was categorized as high, showing a significant difference between the pretest and posttest scores. The T-Test produces a Sig value. (2-tailed) of 0.00 <0.005 and tcount > ttable of 28.956 > 2.04523, which shows a significant increase in learning outcomes.